아파트단지 조경 공사비의 공종별 경년변화 특성 분석 -공공기관 시행의 수도권 아파트단지를 중심으로 - 박상진; Sang Jin Park; 조세환; Se Hwan Cho (한국조경학회지, 2015)
본 연구는 우리나라의 대표적 아파트단지 조성 공공기관인 ‘J’공사를 대상으로 조경 식재 및 시설물 공종별 공사비산정 비율 및 그들의 경년변화 특성 분석을 통해 향후 보다 합리적인 조경공사비 산정을 위한 기초 자료 제시를 목적으로 수행하였다. 연구의 대상 및 자료는 2004년부터 2012년까지 수행한 수도권 아파트단지 37개 현장의 조경식재 및 시설물공사비를 대상으로 하였다. 경년변화 특성 분석을 위해 기술분석, 상관분석 등 통계분석 방법을 사용하였으며 다음과 같은 결론이 도출되었다. 첫째, 2004년부터 2012년까지 9년간 시행된 조경공사 비용 중 식재공사비와 시설물공사비의 평균 비율은 56.1% 대 43.9%인 것으로 나타났다. 둘째, 식재공사와 시설물공사 모두 약 ±3%의 변동 폭에 국한되고 있어물가상승률 등을 감안하며 거의 상대적 변화가 없는 특징을 보이고 있었다. 셋째, 조경공사 공종별 공사비 투입에서는 최소 ±1%에서 최대 ±5%의 변동폭(變動幅)을 보임으로써 조경공사비에서는 시설물공사비가 경년별 변화의 폭이 상대적으로 높은 특징을 보이는 것으로 나타났다. 넷째, 이상과 같이 경년별, 조경공종별 조경공사비의 비율이 일괄적으로 나타나는 것은 아파트단지의 지역적 특성과 입지여건 등의 조건을 반영하지 못하는 한계가 있었음을 알 수 있었다. 다섯째, 조경공종별 조경 요소별 상관관계가 높게 나타남으로써 전체적인 공사비 틀 안에서 공사비간의 부분적 조정을 통해 전체 조경공사비를 통제하고 있는 것으로 나타났다. 이상의 결과는 조경공사비가 이용자들의 만족이나, 아파트단지의 여건 등의 환경적 특성과 상관없이 획일적으로 책정되고 있다는 문제점을 제시하고 있었다. This study was conducted for the purpose of presenting basic data for calculating a more reasonable landscaping project cost in the future through the construction cost calculation ratio of scenic planting and facilities and their time series trend analysis targeting ``J`` corporation, a representative Korean public institution that creates apartment complexes. This study targeted scenic planting and the facility construction costs of 37 apartment complexes in the capital area from 2004 to 2012, using statistical analysis methods such as technical analysis, correlation analysis, and regression analysis to analyze the characteristics of the time series change. The conclusion was drawn as follows. First, breaking down the cost of overall landscaping projects to scenic planting and facility construction, the ratio of the average cost of scenic planting to that of facility construction showed 56.1% to 43.9% from 2004 to 2012. Second, the costs of planting construction and facility construction both showed a fluctuation range of about ±3%, implying relatively steady costs considering the inflation rate. Third, the landscape construction cost for each type of construction resulted in a fluctuation range from minimum ±1% (exercise facility) to maximum ±5%(packing facility), reflecting that among the landscaping projects, the facility construction costs tended to show relatively large fluctuations in accordance with the change of time series. Fourth, the comprehensive indication of the ratio of landscaping project costs by time series and landscaping construction type implies that the regional characteristics and positional condition of the apartment complexes were not reflected sufficiently. Fifth, the high level of correlation of landscaping construction types and landscaping construction elements imply that the entire construction costs were controlled through partial adjustment of cost components within the overall frame of construction cost. These results reveal the problems of standardized landscaping cost irrespective of user satisfaction or environmental traits such as the conditions of the apartment complexes.